A survey on ceramic radome failure types and the importance of defect determination. (July 2023) - Saliha Fidan, Şeyma; Ünal, Rahmi
Highlights: Failure types of ceramic radomes. Application of the Weibull Method in Ceramics. Subsurface damage formation and detection: Destructive and Non-destructive Methods. Radome test systems: Thermo-Structural Test System, Rain Erosion Test Systems. Abstract: A missile is a tube-shaped air vehicle that travels long distances through the air and has a radio frequency seeker that exchanges signal with radar against possible threats. A structure called a radome is placed on the missile nose, and it protects the seeker antenna from the external environment. The radome material must have electromagnetic permeability, high thermal shock resistance, and a certain level of strength to maintain its integrity under flight conditions. Ceramic materials with the optimum combination of these properties are preferred as missile radome materials. Ceramic radomes are also expected to be erosion-resistant and maintain their structural stability along with the thermal and structural loads. Since the increasing competition conditions require reaching higher missile speeds (Ma > 5) today, a radome is needed to develop resistant to these speeds. Under harsh flight loads on the radome can cause severe damage that may lead to fracture. This review study discusses the literature on radome failure types, the effects of structural defects on radome failure, and the importance of defect determination. It is found that thermal and mechanical loads can cause catastrophic fractures at the connection point of the radome with the missile body, which is the most critical failure type. Detecting structural defects like micro cracks is vital for high-quality radome production. The number of micro-cracks formed during the production of radomes increases with an increase in part size. For this reason, coupon tests are insufficient to detect the behavior of large-volume parts. Consequently, statistical methods such as the Weibull distribution determine the damage-based radome behavior. Another critical issue for a radome is to verify its structural integrity, and ground tests should be applied to prevent possible failure during flight tests. In conclusion, this review provides researchers with a general and future perspective about possible failure types, defect detection methods, and ground test systems for ceramic radome.